2015
DOI: 10.1080/00222348.2015.1029419
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effect of Semi-Acetal Formation on the Properties of Dialdehyde Starch and its Thermoplastic Blend with Glycerol

Abstract: Dialdehyde sweet potato starch (DASS) with various aldehyde contents was prepared and the properties analyzed in terms of solubility, intrinsic viscosity, scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The results demonstrated that when the aldehyede content of DASS was increased from 20% to 95%, the solubility, molecular weight, crystallizability, and thermal stability decreased. Thermoplastic DASS (TPDASS) was prepared by adding glycerol as a plasticizer; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This suggests that the thermosetting plastic generated could form an inter-and intramolecular acetal and hemiacetal crosslinking network during the hot compression molding process for sheet production [25,26]. Furthermore, as previously reported, aldehyde materials can establish network linkages with hydroxyl functional groups [68][69][70]. Thus, while glycerol acts as a plasticizer, it may also engage in acetal linkage formation with dialdehyde starch.…”
Section: Mechanical Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…This suggests that the thermosetting plastic generated could form an inter-and intramolecular acetal and hemiacetal crosslinking network during the hot compression molding process for sheet production [25,26]. Furthermore, as previously reported, aldehyde materials can establish network linkages with hydroxyl functional groups [68][69][70]. Thus, while glycerol acts as a plasticizer, it may also engage in acetal linkage formation with dialdehyde starch.…”
Section: Mechanical Propertiessupporting
confidence: 65%
“…The proposed linkage structure of thermosetting plastic derived from dialdehyde pineapple starch is visualized in Figure 9. Notably, the highest strength values achieved by the thermosetting plastic, prepared using dialdehyde pineapple starch in this study, surpass those of other aldehyde starch-based plastics, which typically fall within the range of 2 MPa to 30 MPa [53,69]. The densities of the starch-based plastics were also monitored, as depicted in Figure 10b.…”
Section: Mechanical Propertiesmentioning
confidence: 74%
See 1 more Smart Citation
“…In previous studies, based on the high functionality and reactivity of aldehyde groups, there have been attempts to use environment-friendly and non-toxic dialdehyde carbohydrates as crosslinking agents to replace glutaraldehyde. The linkages between aldehyde and hydroxyl groups are used to prepare films [25,26] while the linkages between aldehyde and amine groups are used to prepare films or gels and fix biological tissues [27,28,29]. Citric acid, which is environment-friendly, non-toxic, and biodegradable, is used as an excellent crosslinking agent in the food and drug industry [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dialdehyde yam starch has poor stability as compared to native starch when the content of the aldehyde groups is increased [12]. A recent study has also suggested that thermal stability of dialdehyde sweet potato starch will decrease when the aldehyde content was increased from 20% to 95% [13]. Therefore, knowing how to further improve the thermal stability of DAS is deserving of research.…”
Section: Introductionmentioning
confidence: 99%